Pelatihan Pembuatan Flyer sebagai Keterampilan Digital Abad ke-21 bagi Mahasiswa PGSD dan Guru SD - DAMARISWARA, RIAN; Mukmin, Bagus Amirul; Permana, Erwin Putera; Wiguna, Frans Aditia; Imron, Ilmawati Fahmi; Putri, Kharisma Eka; kurnia, Ita (Universitas Nusantara PGRI Kediri, 2022)
The skills of prospective teachers and elementary school teachers in operating digital-based technology are still very low. It has been proven that there are still many teachers who have not used digital applications in the learning process, outreach to parents regarding school programs, and school activities. This service aims to provide digital training related to making flyers as a medium for socialization and learning in elementary schools for prospective teachers and elementary school teachers. The service was carried out using the training method which was attended by 353 PGSD students and elementary school teachers. The training was carried out offline and online. As a result of the training, participants gave positive attention to the training they attended. This is evidenced by more than 50% of the participants filling out the questionnaire with a score of 4. This means that participants who were previously unfamiliar with technology have become knowledgeable. Nonetheless, there were deficiencies in the implementation of the training. Training should be carried out 100% offline with ideal participant capacity